IMPROVING MATHEMATICS LEARNING IN UNDERSTANDING FLAT BUILDINGS THROUGH PICTURE MEDIA FOR STUDENTS WITH MODERATE TUNAGRAHITA CLASS IV SDLB IN SLB NEGERI 2 CENTRA PK-PLK CIMAHI CITY - Turliah, Eulis (Journal Of Educational Experts (JEE), 2023)
Moderate tunagrahita children are children who have limitations in intellectual function (IQ). This study aims to describe the process of learning mathematics in class IV SDLB with moderate impairment in terms of planning and implementation of learning in the classroom. Learning to recognize flat shapes in moderate tunagrahita children is expected to make it easier for students to learn, add insight, inspire, develop various character values, increase knowledge and develop student abilities. This research method uses descriptive qualitative research methods because the main data sources of this research are observation and documentation. The results of this study are expected that math learning can add information or insight for teachers so that they can make learning better and achieve maximum. From the results of the study, the researcher proposes recommendations / suggestions for teachers to provide selection of learning materials that are in accordance with the needs of children so that students can understand learning materials easily. The success in this Classroom Action Research (PTK) is seen in each cycle, namely in Cycle I by 60% and increased in Cycle II to 100%..